Consumer price index manual : theory and practice - Turvey, Ralph ([International Labour Office], 2004)
The consumer price index (CPI) measures the rate at which the prices of consumer goods and services are changing over time. It is a key statistic for economic and social policymaking and has substantial and wide-ranging implications for governments, businesses, and households. This important and comprehensive Manual provides guidelines for statistical offices and other agencies responsible for constructing CPIs, and explains in-depth the methods that are used to calculate a CPI. It also examines the underlying economic and statistical concepts and principles needed for making choices in efficient and cost-effective ways, and for appreciating the full implications of those choices.
"This volume is an expanded revision of Consumer price indices: An ILO manual, published in 1989"--Page v
The opening Web page contains links to each chapter in PDF form.
Title from Web page (viewed June 23, 2005).
Publication from: International Labour Organization website.
Keywords: Consumer price indexes.; Prices.; Indice des prix à la consommation.; Prix.; prices.; BUSINESS & ECONOMICS -- Economics -- Microeconomics.; Consumer price indexes; Prices; Cost of living indices -- -- Statistical methodology; Price indices -- -- Statistical methodology